Bureaucratization, education and the meanings of responsibility. Issue 5 (28th December 2018) - Spector, Hannah
Abstract: In US-based educational research, the bureaucratization of education has been interpreted primarily from economic points of view. This paper examines bureaucracy and education from a political perspective, which provides key insights into the ways that bureaucracy as a form of governance influences ethical consciousness. As this paper puts forth, bureaucratic socialization supplants procedural for ethical responsibility. To understand the gravity and pervasiveness of this process, I turn to Max Weber's theory of rational bureaucracy and Hannah Arendt's insights into bureaucracy as a type of political domination, which she calls 'rule by Nobody'. Following Arendt, bureaucracy is the most tyrannical type of rule given that there is tyranny without a tyrant. As such, responsibility falls by the wayside since no one can answer for what is being done. I argue that to understand the meanings of responsibility in education, one must do so in light of the ways that universal bureaucratization – its rational procedures, managerial techniques, knowledge fragmentations and so on – undermines ethical consciousness. As understanding rests at the heart of this inquiry, the paper ends on a note of caution regarding what to do about the breakdown of educational responsibility in a bureaucratized society.